White Light Spectral Interferometry as a Spectrometer Calibration Tool. Issue 5 (May 2014) - de la Fuente, Raúl
For this paper, we used a white light interferometer in combination with spectral lamps to perform the wavelength calibration of a dispersive spectrometer. Illuminating the spectrometer with suitable spectral lamps gives the wavelength-pixel number relationship at discrete positions of the spectrometer detector array, and the wavelength-dependent phase difference at the output of the white light interferometer allows for a complete spectral calibration at any point on the detector (i.e., for every wavelength in the spectral range of the spectrometer). The details of this new calibration procedure are discussed, and two practical examples exhibiting the robustness of the method are presented. In addition, certain issues relating to minimizing the number of spectral lines used in the calibration procedure are examined.